Surface modification of Al-7075 using Cu-CNT green tool in EDM. (4th March 2022) - Madhab Barua, Bhargab; Rahang, Maneswar
ABSTRACT: Now-a-days carbon nanotube (CNT) is widely used because of its inimitable properties such as high electrical and thermal conductivities, high tensile strength, etc. In this work, an attempt has been made to modify the surface of Al-7075 alloy using Cu-MWCNT powder metallurgy green compact tool in the electric discharge machining process. The effects of contributing parameters i.e. peak current ( I p ), voltage and compact load (CL) have been investigated with respect to performance measures such as, Material Deposition Rate (MDR), Tool Wear Rate (TWR) and Surface Roughness (Ra). The modified surface has been assessed by optical microscopy, FESEM, XRD and EDS analyses. Highest MDR of 0.15 mg min –1, lowest TWR of 2.05 mg min –1 and lowest Ra of 2.57 µm have been attained. The deposition of tool materials has improved the microhardness up to 2.6 times than that of base material.